2021
DOI: 10.5603/pjnns.a2021.0039
|View full text |Cite
|
Sign up to set email alerts
|

Neurological symptoms in hospitalised patients with COVID-19 and their association with in-hospital mortality

Abstract: Objectives. To evaluate the spectrum of neurological symptoms in patients with COVID-19 during the first 14 days of hospitalisation and its association with in-hospital mortality. Material and methods.We included 200 patients with RT-PCR-confirmed COVID-19 admitted to University Hospital in Krakow, Poland. In 164 patients, a detailed questionnaire concerning neurological symptoms and signs was performed prospectively within 14 days of hospitalisation. In the remaining 36 patients, such questionnaires were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
2
18
1
5
Order By: Relevance
“…The incidences of at least one new-onset neurological signs/symptoms in the context of COVID-19 infection were extremely wide-ranging, i.e., ~ 12 to ~ 85%. The wide extent of these percentages was based on retrospective and prospective studies from various countries: Austria (Zifko et al 2021); China (Mao et al 2020;Xiong et al 2020) Egypt (Khedr et al 2021); Iran (Amanat et al 2021;Ghaffari et al 2021); Italy (Benussi et al 2020;Rifino et al 2021;Travi et al 2021); France (Kremer et al 2020); Germany (Fleischer et al 2021); Mexico (Flores-Silva et al 2021); Pakistan (Iltaf et al 2020); Poland (Wnuk et al 2021); Portugal (Oliveira et al 2021); South Korea (Kim et al 2021);Spain (García-Azorín et al 2021a, b;García-Moncó et al 2020;García-Azorín et al 2021a, b;Romero-Sánchez et al 2020); Turkey (Karadaş et al 2020;Yuksel et al 2021); United States of America (Chachkhiani et al 2020;Eskandar et al 2021;Frontera et al 2021;Liotta et al 2020); multinational (Chou et al 2021). Systematic reviews with or without meta-analysis (Cagnazzo et al 2021;Chua et al 2020;Collantes et al 2021;Pinzon et al 2020;Romoli et al 2020;Tsai et al 2020;Vakili et al 2021) and narrative/ scoping reviews (Ahmed et al 2020;Maury et al 2021;Roy et al 2021...…”
Section: Discussionmentioning
confidence: 99%
“…The incidences of at least one new-onset neurological signs/symptoms in the context of COVID-19 infection were extremely wide-ranging, i.e., ~ 12 to ~ 85%. The wide extent of these percentages was based on retrospective and prospective studies from various countries: Austria (Zifko et al 2021); China (Mao et al 2020;Xiong et al 2020) Egypt (Khedr et al 2021); Iran (Amanat et al 2021;Ghaffari et al 2021); Italy (Benussi et al 2020;Rifino et al 2021;Travi et al 2021); France (Kremer et al 2020); Germany (Fleischer et al 2021); Mexico (Flores-Silva et al 2021); Pakistan (Iltaf et al 2020); Poland (Wnuk et al 2021); Portugal (Oliveira et al 2021); South Korea (Kim et al 2021);Spain (García-Azorín et al 2021a, b;García-Moncó et al 2020;García-Azorín et al 2021a, b;Romero-Sánchez et al 2020); Turkey (Karadaş et al 2020;Yuksel et al 2021); United States of America (Chachkhiani et al 2020;Eskandar et al 2021;Frontera et al 2021;Liotta et al 2020); multinational (Chou et al 2021). Systematic reviews with or without meta-analysis (Cagnazzo et al 2021;Chua et al 2020;Collantes et al 2021;Pinzon et al 2020;Romoli et al 2020;Tsai et al 2020;Vakili et al 2021) and narrative/ scoping reviews (Ahmed et al 2020;Maury et al 2021;Roy et al 2021...…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of respiratory muscles can lead to myasthenic crisis, a life-threatening condition that requires intensive care and respiratory support [3]. On the other hand, fatigue and muscle weakness as well as respiratory failure are cardinal symptoms of Coronavirus disease 2019 (COVID-19) [4,5]. Therefore, it can be very challenging to distinguish between these two conditions as well as to diagnose MG exacerbation during a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection [6].…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the COVID-19 pandemic, growing evidence has indicated that patients with SARS-CoV-2 may develop neurological symptoms (Tab. 1) [7,28]. It has been established that the major factors associated with the neurological complications of SARS-CoV-2 infection were firstly age over 60, and secondly a history of neurological conditions.…”
Section: Neurological Symptoms Of Covid-19mentioning
confidence: 99%
“…Anosmia and ageusia were reported in 21.5% and 27% of patients, respectively. Moreover, analysis of a possible association of neurological symptoms with inhospital mortality revealed that a decreased level of consciousness and delirium were linked to a higher risk of death during hospitalisation [34].…”
Section: Neurological Symptoms Of Covid-19mentioning
confidence: 99%